The Practice Of Zakat Worship As An Application Of Islamic Religious Education To The Fisherman Community Of Harapan Island In Jeneponto Regency, South Sulawesi - Rahman, Abdul; Mutakabbir, Abdul (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
This research describes the practice of Zakat as an application of Islamic religious education to the fishermen community of Harapan Island. The method used to get data is structured interviews. The description uses theological and sociological approaches. The results reveal theoretically, the people of Harapan Island are not proficient in explaining the meaning of Zakat worship, even though their practice is inversely proportional. They are a religiously devout society, trying to fulfill all the obligations ordered by Allah. That is proven by continuing to pay Fitrah Zakat and assets Zakat even though they are in a mediocre state. Education with the practice of Zakat worship is to give an example first, then inform the family of the benefits according to religion, health, and social when fulfilling obligations, especially the three Zakat services. Furthermore, advise family members if they don't fulfill it and provide training according to their respective abilities.